Auditory/visual distance estimation: accuracy and variability - Anderson, Paul W.; Zahorik, Pavel (Frontiers in Psychology, 2014)
Past research has shown that auditory distance estimation improves when listeners are given the opportunity to see all possible sound sources when compared to no visual input. It has also been established that distance estimation is more accurate in vision than in audition. The present study investigates the degree to which auditory distance estimation is improved when matched with a congruent visual stimulus. Virtual sound sources based on binaural room impulse response (BRIR) measurements made from distances ranging from approximately 0.3 to 9.8 m in a concert hall were used as auditory stimuli. Visual stimuli were photographs taken from the listener’s perspective at each distance in the impulse response measurement setup presented on a large HDTV monitor. Listeners were asked to estimate egocentric distance to the sound source in each of three conditions: auditory only (A), visual only (V), and congruent auditory/visual stimuli (A+V). Each condition was presented within its own block. Sixty-two listeners were tested in order to quantify the response variability inherent in auditory distance perception. Distance estimates from both the V and A+V conditions were found to be considerably more accurate and less variable than estimates from the A condition.